Discovery of novel and highly potent small molecule inhibitors targeting FLT3-ITD for the treatment of acute myeloid leukemia using structure-based virtual screening and biological evaluation - Shi, Kun; Hong, Ye; Liu, Huajing; Yang, Xiaotian; Wang, Fengzhen; Zhang, Yanming (Frontiers in Pharmacology, 2025)
Considering the essential role of FLT3-ITD mutations in the development of acute myeloid leukemia (AML), the research and development of FLT3 inhibitors hold significant therapeutic potential. In this study, we identified a novel, highly potent small molecule inhibitor, FLIN-4, targeting FLT3 through structure-based virtual screening. Notably, FLIN-4 showed exceptional inhibitory effects in kinase activity inhibition assays, exhibiting a potent inhibitory effect against FLT3 (IC50 = 1.07 ± 0.04 nM). This potency was significantly superior to that of the known positive inhibitor Midostaurin, showing approximately 27 times higher inhibitory potency. Molecular dynamics simulations have confirmed the stable interaction between FLIN-4 and FLT3. Furthermore, cytotoxicity assays revealed that FLIN-4 has significant anti-proliferative activity against the AML cell line MV4-11 (IC50 = 1.31 ± 0.06 nM). Overall, these data suggest that FLIN-4, as a potential therapeutic candidate for AML, is valuable for further research and development.